The Pairwise Correlated Generalized Valence Bond Model of Electronic Structure I; The Estimation of Pair Energies from Orbital Overlaps - Petersson, G. A. (1974)
A new method for the accurate a priori calculation of atomic and molecular energies is proposed. The new method agrees with experiment to within less than 1 kcal/mole in all cases examined thus far, and is applicable to excited states and to transition states for chemical reactions. Since the new method corrects the results of generalized valence bond calculations for the effects of electron pair correlations, we call the new method the pairwise correlated generalized valence bond method.